Examining corporate reputation management in a local municipality in the Vaal region: a case study - Mokaeane, Sibongile Bernadette (Vaal University of Technology, 2017)
BACKGROUND: Corporate reputation refers to an organisation’s past and present action, which has a huge impact on how the organisation is viewed by its internal and external stakeholders. In the context of business organisation, the importance of reputation in public service and government organisations needs to be recognised, especially in South Africa, where many problems are associated with local government. Coupled with this, there has been lack of emphasis on collaborative consultation processes and participation by the communities in matters that affect them. OBJECTIVE OF THE STUDY: The purpose of this qualitative, interpretive study was to analyse personal experiences of employees at a local municipality, on the management of corporate reputation. Systems theory was adopted as a theoretical framework for the study. METHOD: This research employs a qualitative research method and a case study design. The qualitative research was relevant for this research as it is naturalistic, which is research based in natural settings where communication occurs. The in-depth individual, semi structured interviews enabled the researcher to get rich information from the participants, who are employees of the municipality and work within the broad frame of public relations, communications, event management and marketing. These participants engage with the external stakeholders on events management or on expertise, leadership and management skills with regard to corporate reputation management. RESULTS: The results reveal that management of reputation is probably a multifaceted concept. Hence corporate social responsibility, emotional appeal, financial performance, products and services, vision and leadership and workplace environment all feature but it is unlikely that the participants perceive reputation as separate from image and identity as they use the terms synonymously. The responses reveal that a systems view of an organisation, being social in a social system, indicate that the various components in the internal environment cannot be separated from the external environment as they are continuously and dynamically interacting with one another with corporate communication acting as a ‘glue’, which holds them together. Corporate communication is thus an essential part of the system as it serves to align the organisation’s vision, culture and image that people have of an organisation.
M. Tech. (Department of Public Relations Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Corporate reputation management; Local municipality; Corporate social responsibility; Public relations; Communication and stakeholders; Dissertations, Academic -- South Africa.; Local government -- South Africa.; Social responsibility of business.; Municipal government -- Public relations.; Municipal services -- South Africa.; Municipal government -- South Africa.